The Marketing Communication Mix Strategies of a Quick Service Restaurant - Rebulanan, Maria Lourdes F. (International Journal of Psychosocial Rehabilitation, 2020)
This study sought to assess the level of effectiveness of the marketing communication mix strategies of a Quick Service Restaurant in selected stores in Sta. Mesa. This study used the quantitative-descriptive method with a duly validated questionnaire as research instrument. Convenience sampling was employed. Data were drawn from 400 respondents who are consumers of a known Quick Service Restaurant in selected Sta. Mesa branches. The respondents’ assessment on the level of effectiveness of the different Marketing Communication Mix Strategies revealed “Very Effective” in terms of Advertising and Direct Marketing, and “Effective” in areas of Sales Promotion, Publicity/Public Relations, and Personal Selling. There is no significant difference on the level of effectiveness when grouped according to age and average monthly income. According to sex, there is a significant difference in terms of advertising. Whereas, according to Civil Status, there is a significant difference in Personal Selling; According to Highest Educational Attainment, there is a significant difference in the area of Sales Promotion and Publicity/Public Relations. Lastly, according to Frequency of visit to the store, there is a significant difference in terms of Publicity/Public Relations and Personal Selling. Majority of the respondents aged 21-30 years old, mostly females, single, earning an average monthly income of 11,000.00-20,000.00, college graduates, and frequents the store once to thrice a month. It is recommended for this QSR to be more audacious in raising public awareness on the different Public Relations activities to strengthen more its brand image which can lead to brand loyalty.